2015
DOI: 10.1149/06604.0039ecst
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Anisotropic Biaxial Stress in Si1-X Ge x /Ge Mesa-Structure by Oil-Immersion Raman Spectroscopy

Abstract: Si1-x Ge x is one of the prospective materials for the next-generation transistors due to its high carrier mobility, especially for high Ge concentration Si1-x Ge x . Inducing strain in the Si1-x Ge x leads to transistor performance improvement, however it is difficult to evaluate strain induced in the channel region because the strained Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…TO 1 and TO 2 can be excited in the oil-immersion technique owing to z-polarization, although only the LO phonon is detected under the conventional backscattering geometry from the (001)-oriented Si and SiGe. 6,21,24,25,35,36) To obtain multi stress components, e.g., anisotropic biaxial stresses perpendicular and parallel to the line in the SiGe layer, one requires at least more than two optical phonons, which can be achieved by oil-immersion Raman spectroscopy.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…TO 1 and TO 2 can be excited in the oil-immersion technique owing to z-polarization, although only the LO phonon is detected under the conventional backscattering geometry from the (001)-oriented Si and SiGe. 6,21,24,25,35,36) To obtain multi stress components, e.g., anisotropic biaxial stresses perpendicular and parallel to the line in the SiGe layer, one requires at least more than two optical phonons, which can be achieved by oil-immersion Raman spectroscopy.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Using these optical phonon modes, the information of anisotropic biaxial stress states can be obtained. [23][24][25][26][27] The oil-immersion technique has been performed for the accurate evaluation of anisotropic biaxial stress states in various materials applied to nanostructure devices. 6,[22][23][24][25][26][27][28][29] In this study, we evaluated the anisotropic stress states in the compressively strained SiGe layers on the Si substrates fabricated by a selective ion implantation technique using oil-immersion Raman spectroscopy and revealed that the anisotropy of biaxial stress states depends on the stripe-width ratio of ion-implanted and unimplanted areas.…”
Section: Introductionmentioning
confidence: 99%
“…12) In particular, it has been reported that Raman spectroscopy is a powerful strain evaluation technique, because it has advantages such as a nondestructive measurement and a high spatial resolution. [13][14][15][16][17][18][19][20][21] To evaluate strain in Si 1−x Ge x by Raman spectroscopy quantitively, phonon deformation potentials (PDPs) are necessary for a conversion from a Raman wavenumber shift to a stress value. [22][23][24][25] PDPs indicate a relationship between strain tensor and force constant tensor.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] For each device, several parameters in the thin SiGe film should be optimized, e.g., strain, crystal quality, impurity, temperature, and composition, for which Raman spectroscopy can be a powerful tool as many researchers have demonstrated it. [11][12][13][14][15][16][17][18][19][20][21][22][23] Actually, SiGe exhibits interesting features in the Raman analysis. The crystal structure of SiGe is that of a diamond and can hold the whole Ge or Si concentration range in the matrix.…”
mentioning
confidence: 99%
“…32,33) Since the tensile stress is induced in the strained SiGe film, the longitudinal mode appears on the lower wavenumber side compared with the transverse one. 18) Figure 2 shows the Raman spectrum of pure Ge with a Lorentz fitting curve. As shown in this figure, the residue can be found on the low-wavenumber side of the first-order peak, which was observed as the broad peaks for the Ge-rich SiGe, as shown in Fig.…”
mentioning
confidence: 99%